Відображення збору й обробки інформації про трансакційні витрати в системі обліку - Бонарев, Володимир (Економіка та суспільство, 2022)
The article considers the essence of the synergistic direction of research. The need for improved accounting systems is determined by developing recommendations for expanding information on transaction costs, related to the improvement of the entity's work in general and accounting in particular. It was clarified that the problem of ac-counting display of transaction costs on accounts of the accounting system is that each accounting facility contains a share of transaction costs, that is, this type of expense is distributed among different parts of the property and obli-gations of the enterprise. Various approaches of research scientists regarding methods of collecting and processing information of transaction costs in the accounting system are disclosed. The analysis of the methods under consider-ation shows that many of them reflect transaction costs only in operating activities, and this is not quite correct, since transaction costs also arise in financial and investment activities. In addition, scientists do not take into account the full list of transaction costs, arising in the enterprise, which leads to the receipt of inaccurate and incomplete infor-mation about the ways of their occurrence in the accounting system. Since transaction costs are distributed among a large number of accounts and it is difficult to distinguish such costs, which leads to the implementation of labor-in-tensive work by responsible employees, it is indicated that it is impractical to allocate a separate account to reflect transaction costs in the billing system. The main requirements for sources of information on transaction costs in the accounting system are highlighted (comparability; objectivity and reliability; completeness; accessibility). It is noted that the submitted requirements allow the areas of responsibility to make decisions more quickly and more efficiently analyze transaction costs. It is determined that in any accounting program intended for automation of enterprise ac-counting, it is necessary to add information (module) about transaction costs. The grouping of transaction costs for the purposes of automated accounting into four blocks is proposed and their essence is disclosed.
DISPLAYING THE COLLECTION AND PROCESSING OF INFORMATION ON TRANSACTION COSTS IN THE ACCOUNTING SYSTEM
Keywords: accounting, accounting system, costs, transaction costs, synergistic approach